2017
DOI: 10.1038/srep43998
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Pressure Chemical Ionization Gas Chromatography Mass Spectrometry for the Analysis of Selected Emerging Brominated Flame Retardants in Foods

Abstract: Emerging brominated flame retardants (eBFRs) other than polybrominated diphenyl ethers (PBDEs), polybrominated biphenyls (PBBs) and their derivatives in foods have been in focus in recent years due to their increasing production volumes, indefinite information on toxicities and the lack of data on occurrence in environments, foods as well as humans. In this study, gas chromatography was coupled to an atmospheric pressure chemical ionization-tandem mass spectrometry (APGC-MS/MS) for the analysis of six eBFRs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…38 The concentrations of HBB, PBT, and BTBPE in chicken from four different places of China (Sichuan, Fujian, Jilin, Henan) were in the range of nd−4.3, nd−48.7, and 20.1−80.9 pg/g ww, respectively (Table 2). 120 In human milk from three European countries (Norway, The Netherlands, Slovakia), mean concentrations of HBB and PBT were 0.036−0.048 and 0.028−0.049 ng/g lw, respectively, and PBEB were rarely found (detection rate in human milk: Norway 2%, The Netherlands 0%, Slovakia 3%) (Table 2). 121…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…38 The concentrations of HBB, PBT, and BTBPE in chicken from four different places of China (Sichuan, Fujian, Jilin, Henan) were in the range of nd−4.3, nd−48.7, and 20.1−80.9 pg/g ww, respectively (Table 2). 120 In human milk from three European countries (Norway, The Netherlands, Slovakia), mean concentrations of HBB and PBT were 0.036−0.048 and 0.028−0.049 ng/g lw, respectively, and PBEB were rarely found (detection rate in human milk: Norway 2%, The Netherlands 0%, Slovakia 3%) (Table 2). 121…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…In addition, we show that of a commercial atmospheric pressure gas chromatography/mass spectrometry (APGC/MS) source can be used with this reagent ion to carry out ambient ionization MS. APGC/MS was first developed in the 1970s 52,53 and has been applied to the analysis of a number of toxic organic compounds, 54 including pesticides, [55][56][57] polycyclic aromatic hydrocarbons (PAHs) and nitro-PAHs, 58-60 dioxins [61][62][63] and brominated flame retardants. 64 We show here that the source can be used in stand-alone mode, i.e. without the GC interface, for ambient gas analysis.…”
Section: Introductionmentioning
confidence: 94%
“…Inhalation is the primary route of human exposure to OPFRs. Several studies have reported the ubiquitous occurrence of chloro-, alkyl-, and aryl-substituted OPFRs (Cl-OPFRs, alkyl-OPFRs, and aryl-OPFRs) in PM 2.5 samples worldwide, including in Stockholm, Sweden, Toronto, Canada, an e-waste site in Pakistan, and a few cities in China. However, previous studies using gas chromatography electron ionization mass spectrometry (GC-EI-MS) to analyze OPFRs have limited investigation capability on the whole contamination profiles of OPFRs and their fate and transformation in the atmosphere due to inadequate specificity and sensitivity. Recently, gas chromatography–atmospheric pressure chemical ionization tandem mass spectrometry (GC-APCI-MS/MS) has gained attention for the analysis of trace environmental pollutants such as dioxins, brominated flame retardants, and polyaromatic hydrocarbons . Compared to conventional EI and CI sources, APCI is softer and can produce more intense protonated or deprotonated quasi-molecular ions, providing improved selectivity and sensitivity through a high signal-to-noise (S/N) ratio and higher detection accuracy.…”
Section: Introductionmentioning
confidence: 99%